The New Totalitarians: The Swedish COVID-19 strategy and the implications of consensus culture and media policy for public health - Martin Lindström (Elsevier, 2021)
Aims: The aim is to discuss implications of consensus culture in combination with media policy in Sweden with regard to the Swedish COVID-19 strategy in the spring of 2020. Methods: Investigation of prerequisites for scrutiny by the Swedish mass media of the Swedish strategy in the spring of 2020 based on discussion regarding consensus culture, media structure and postmodernism in science, politics and administration. Results: The Swedish strategy entailed strong initial confidence in herd immunity (although not officially stated), individual responsibility, evidence based medicine and substantial neglect to cooperate internationally. The strategy may be regarded partly as a result of the postmodern view of science and society predominant in Sweden. A tradition of top down consensus culture combined with mass media's financial and partly structural dependence of the state may help explain the comparative lack of critical questions regarding the strategy at the press conferences in the spring of 2020. Conclusions: Mass media in Sweden should become more financially and structurally independent of the state. The reporting by Swedish media in the spring of 2020 should be subject to peer-reviewed research.